From Mediterranean to Scandinavia—timing and body mass condition in four long distance migrants - Barboutis, Christos; Larsson, Leo; Steinholtz, Åsa; Fransson, Thord (Ornis Svecica, 2015)
In spring, long-distance migrants are considered to adopt a time-minimizing strategy to promote early arrival at breeding sites. The phenology of spring migration was examined and compared between two insular stopover sites in Greece and Sweden for Icterine Warbler, Wood Warbler, Spotted Flycatcher and Collared Flycatcher. All of them migrate due north which means that some proportion of birds that pass through Greece are heading to Scandinavia. The Collared Flycatcher had the earliest and the Icterine Warbler the latest arrival time. The differences in median dates between Greece and Sweden were 3–4 weeks and the passages in Sweden were generally more condensed in time. The average overall speed estimates were very similar and varied between 129 and 137 km/d. In most of the species higher speed estimates were associated with years when birds arrived late in Greece. After crossing continental Europe birds arrive at the Swedish study site with significantly higher body masses compared to when they arrive in Greece and this might indicate a preparation for arriving at breeding grounds with some overload.